2017
DOI: 10.1155/2017/5180707
|View full text |Cite
|
Sign up to set email alerts
|

Helicteric Acid, Oleanic Acid, and Betulinic Acid, Three Triterpenes from Helicteres angustifolia L., Inhibit Proliferation and Induce Apoptosis in HT‐29 Colorectal Cancer Cells via Suppressing NF‐κB and STAT3 Signaling

Abstract: Colorectal cancer (CRC) is one of the most common malignancies and most frequent cause of cancer death worldwide. The activation of both NF-κB and STAT3 signaling and the crosstalk between them play an important role in colorectal tumor. Helicteres angustifolia L. is a type of commonly used Chinese medicinal herb and possesses a wide variety of biological activities. In the present study, we investigate the effects of three triterpenes from H. angustifolia (HT) such as helicteric acid (HA), oleanic acid (OA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Recent studies have demonstrated that certain natural therapeutic agents serve an inhibitory role in the genesis, progression and metastasis of various cancer types (37). Betulinic acid, a pentacyclic triterpene, extracted from Zizyphus mauritiana, displayed potency in inhibiting STAT-3 activation, Src kinase, and JAK-1 and -2 (124,125). Furthermore, it has been reported that betulinic acid induces apoptosis in thyroid, breast, lung and colon carcinomas, indicating its potential as a chemotherapeutic agent (124).…”
Section: Advances In Antitumor Therapeutics Targeting Stat-3mentioning
confidence: 99%
“…Recent studies have demonstrated that certain natural therapeutic agents serve an inhibitory role in the genesis, progression and metastasis of various cancer types (37). Betulinic acid, a pentacyclic triterpene, extracted from Zizyphus mauritiana, displayed potency in inhibiting STAT-3 activation, Src kinase, and JAK-1 and -2 (124,125). Furthermore, it has been reported that betulinic acid induces apoptosis in thyroid, breast, lung and colon carcinomas, indicating its potential as a chemotherapeutic agent (124).…”
Section: Advances In Antitumor Therapeutics Targeting Stat-3mentioning
confidence: 99%
“…Both oleanic acid (OA) and ursolic acid (UA) are two representative triterpenoids with certain solubility in water, methanol, ethanol, 2-propanol, and ethyl acetate [ 29 , 30 , 31 , 32 ]. These two compounds have been evidenced to exhibit a variety of activities, including stabilizing liposomal membranes [ 33 ], anti-cancer [ 34 ], anti-diabetes [ 35 , 36 ], anti-inflammation [ 37 ], anti-oxidation [ 2 ], anti-osteoporosis [ 38 , 39 ], etc. In addition, OA is the most abundant potent triterpenoid in FLL with a content ranging from 7.37 to 13.3 mg/g [ 40 ].…”
Section: Phytochemistry Of Fructus Ligustri Lucidimentioning
confidence: 99%
“… 12 , 19 In CRC cells, BA could induce apoptosis through the mitochondrial pathway, 20 inhibited cell growth of CRC cells by downregulating Sp transcription factors in SW480 and RKO cells, 21 or by suppressing NF- κ B and STAT3 signaling in HT29 cells. 22 It has also been reported that BA can function as NF- κ B activator in a number of other cancer cell lines, 23 suggesting that the antitumor mechanisms of BA was dependent on tumor type.…”
mentioning
confidence: 95%